PENERAPAN SISTEM REWARD BERBASIS KINERJA SEBAGAI PENINGKATAN KINERJA KARYAWAN PADA SPBU PT. SUMBER KURNIA MANDIRI - SUFRO, LAILATUS (Jurnal Akuntansi AKUNESA, 2015)
AbstractThis research aims to analyze and explain the indicator in the performance appraisal system, the application of the performance-based reward system, as well as obstacles encountered in the implementation of performance-based reward system in SPBU PT. Sumber Kurnia Mandiri. This research use the draft or a descriptive qualitative research design and data analysis in this study uses descriptive analysis of narrative. The results showed that the performance appraisal of employees at SPBU PT. Sumber Kurnia Mandiri using model Graphic Rating Scale. The application of performance-based reward system at SPBU PT. Sumber Kurnia Mandiri walking pretty well, but there are several obstacles in its implementation.Keywords: Reward System, Employee Performance